2020
DOI: 10.1016/j.immuni.2019.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Signaling through the Inhibitory Fc Receptor FcγRIIB Induces CD8+ T Cell Apoptosis to Limit T Cell Immunity

Abstract: Effector CD8 + T cells are important mediators of adaptive immunity, and receptor-ligand interactions that regulate their survival may have therapeutic potential. Here, we identified a subset of effector CD8 + T cells that expressed the inhibitory fragment crystallizable (Fc) receptor FcgRIIB following activation and multiple rounds of division. CD8 + T cell-intrinsic genetic deletion of Fcgr2b increased CD8 + effector T cell accumulation, resulting in accelerated graft rejection and decreased tumor volume in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 47 publications
(55 reference statements)
14
69
0
Order By: Relevance
“…Emerging evidence has demonstrated that FcγRIIB is expressed on a subset of polyfunctional CD44 hi CD8 + T cells 21,22. To understand whether pathogen stimulation history affects the expression of the inhibitory Fcγ receptor FcγRIIB on memory CD8 + T cells, we probed CD44 hi Thy1.1 + donor‐specific CD8 + T cells elicited by the different infections for expression of FcγRIIB on days 8 and 28.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has demonstrated that FcγRIIB is expressed on a subset of polyfunctional CD44 hi CD8 + T cells 21,22. To understand whether pathogen stimulation history affects the expression of the inhibitory Fcγ receptor FcγRIIB on memory CD8 + T cells, we probed CD44 hi Thy1.1 + donor‐specific CD8 + T cells elicited by the different infections for expression of FcγRIIB on days 8 and 28.…”
Section: Resultsmentioning
confidence: 99%
“…However, emerging evidence suggests that effector CD8 + T cells can express FcγRIIB 21. Work from our group has further shown that not only can effector CD8 + T cells express FcγRIIB but also that this receptor modulates T cell survival in a cell‐intrinsic manner during primary immune responses in models of transplantation and melanoma 22…”
Section: Introductionmentioning
confidence: 95%
“…FGL2 knockdown in mice will be performed in the future. Previous studies have demonstrated that FGL2 could specifically bind to FcγR receptors, including FcγRIIB (41)(42)(43). FcγRIIB is a transmembrane protein that is abundantly expressed on the surface of myeloid cells (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is increasing evidence that T‐lymphocyte populations express FcγR. Some γδ T cells express FcγRIIIa and αβ T cells reportedly express FcγRIIa, FcγRIIb or FcγRIIIa but the significance with respect to effector function mediated by antibody is presently unclear 24‐28…”
Section: Human Fcγr General Propertiesmentioning
confidence: 99%